Combined directed ortho-zincation and palladium-catalyzed strategies: Synthesis of 4,n-dimethoxy-substituted benzo[b]furans - Guilarte, Verónica; Castroviejo, M. Pilar; Álvarez, Estela; Sanz, Roberto (Beilstein Journal of Organic Chemistry, 2011)
A new route to regioselectively dialkoxy-functionalized benzo[b]furan derivatives has been developed from 3-halo-2-iodoanisoles bearing an additional methoxy group, which have been accessed through an ortho-zincation/iodination reaction. Two palladium-catalyzed processes, namely a Sonogashira coupling followed by a tandem hydroxylation/cyclization sequence, give rise to new and interesting dimethoxy-substituted benzo[b]furans.
Keywords: benzo[b]furans; o-zincation; palladium; selectivity